Entropy generation rate minimization for hydrocarbon synthesis reactor from carbon dioxide and hydrogen. (July 2019) - Zhang, Lei; Xia, Shaojun; Chen, Lingen; Ge, Yanlin; Wang, Chao; Feng, Huijun
Highlights: Process of hydrocarbon synthesis from CO2 and H2 in a fixed-bed reactor. With minimum entropy generation rate as the objective function. It is due to heat transfer, frictional flow and chemical reactions. Profile of the heat reservoir temperature outside tube is optimized. A reduction up to 26.29% of entropy generation rate is achieved. Abstract: The process of hydrocarbon synthesis from carbon dioxide and hydrogen in a fixed-bed reactor, a novel approach of converting renewable and distributed energy to high-energy-density liquid hydrocarbon fuels, is designed and optimized thermodynamically in the present study. With the minimum entropy generation rate (EGR) due to heat transfer, frictional flow and chemical reactions as objective function, finite time thermodynamics (or entropy generation minimization) and optimal control theories are applied to find the minimum EGR along with the corresponding optimal paths of the carbon dioxide hydrogenation reactor. The results show that a reduction up to 26.29% can be achieved by optimizing the profile of the heat reservoir temperature outside the tube and inlet conditions, which is mainly due to a compromised decrease in the irreversibilities of chemical reactions and heat transfer. The chemical driving forces of the FT (Fischer-Tropsch) reactions in the optimal reactors decrease considerably compared with those of the reference reactor under the operation of constant heat reservoir temperature. The results obtained in the present study can provide some theoretical guidelines for the optimal thermal design of the real-world reactor of hydrocarbon synthesis process from carbon dioxide and hydrogen.